2016
DOI: 10.1093/cercor/bhv315
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Corticofugal Fiber Targeting by Retinal Inputs

Abstract: Corticothalamic projection systems arise from 2 main cortical layers. Layer V neurons project exclusively to higher-order thalamic nuclei, while layer VIa fibers project to both first-order and higher-order thalamic nuclei. During early postnatal development, layer VIa and VIb fibers accumulate at the borders of the dorsal lateral geniculate nucleus (dLGN) before they innervate it. After neonatal monocular enucleation or silencing of the early retinal activity, there is premature entry of layer VIa and VIb fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 50 publications
12
112
2
Order By: Relevance
“…The micropipette was filled with mineral oil (Thermo Fisher Scientific Inc., Waltham, MA) and attached to a pressure injector (Nanoliter 2010, World Precision Instruments, Sarasota, FL) connected to a pump controller (Micro4 Controller, World Precision Instruments, Sarasota, FL). To target corticothalamic L6, layer 5 (L5), the AC of NTSR1-Cre ( 2225 ) or RPB4-Cre ( 26, 27 ) neonates was injected with “eNpHR3.0” AAV1 (AAV-EF1a-DIO-eNpHR3.0-YFP) (Halorhodopsin-AAV) constructs from UNC Vector Core (Chapel Hill, NC) or Gi-coupled hM4Di DREADDs AAV8 (AAV8-DIO-hSyn-hM4Di-mCherry) (DREADDs-AAV) construct from Addgene (Cambridge, MA). The micropipette carrying the viral particles was first located above the AC at the left hemisphere at 1.5 mm anterior to lambda and just at the edge of the skull’s flat horizon.…”
Section: Methodsmentioning
confidence: 99%
“…The micropipette was filled with mineral oil (Thermo Fisher Scientific Inc., Waltham, MA) and attached to a pressure injector (Nanoliter 2010, World Precision Instruments, Sarasota, FL) connected to a pump controller (Micro4 Controller, World Precision Instruments, Sarasota, FL). To target corticothalamic L6, layer 5 (L5), the AC of NTSR1-Cre ( 2225 ) or RPB4-Cre ( 26, 27 ) neonates was injected with “eNpHR3.0” AAV1 (AAV-EF1a-DIO-eNpHR3.0-YFP) (Halorhodopsin-AAV) constructs from UNC Vector Core (Chapel Hill, NC) or Gi-coupled hM4Di DREADDs AAV8 (AAV8-DIO-hSyn-hM4Di-mCherry) (DREADDs-AAV) construct from Addgene (Cambridge, MA). The micropipette carrying the viral particles was first located above the AC at the left hemisphere at 1.5 mm anterior to lambda and just at the edge of the skull’s flat horizon.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in the absence of retinal input, the exteroceptive visual nucleus LGN receives input from L5B (refs 19, 85), a normally higher-order nucleus-destined afferent, and develops a corresponding higher-order transcriptional identity19. Ascending exteroceptive and descending corticofugal inputs may thus compete to innervate thalamic nuclei.…”
Section: Developmental Emergence and Plasticity Of Neocortical Circuitsmentioning
confidence: 99%
“…We next examined the development of synapses of tdTom+ axons in Po. tdTom+ axons are shown to innervate Po in the first postnatal week (Grant et al, 2016;Hoerder-Suabedissen et al, 2019). tdTom+ boutons, which colocalised with VGluT1, were detected in Po at P8.…”
Section: Layer 5 Giant Boutons In Posterior Thalamic Nucleus Develop mentioning
confidence: 95%
“…Previous studies using injection of anterograde tracers, or Thy1 promotor-driven fluorescence labelling, have shown that layer 5 neurons from S1 cortex have giant boutons in Po of adult brains (Groh et al, 2008;Hoerder-Suabedissen et al, 2018;Hoogland et al, 1991). To study the synaptic development of layer 5 corticothalamic projections, we used the Rbp4-Cre;tdTomato mouse line, whose tdTomato expression starts in a subset of layer 5 neurons at late embryonic stages (Grant et al, 2016;Hoerder-Suabedissen et al, 2019). This allows us to visualise their corticothalamic projections innervating Po in the early postnatal period.…”
Section: Layer 5 Giant Boutons In Posterior Thalamic Nucleus Develop mentioning
confidence: 99%
See 1 more Smart Citation